Temperature-modulated magnetic skyrmion phases and transformations analysis from first-order reversal curve study - Ang, Calvin Ching Ian (2021)
We performed a temperature-modulated first-order reversal curve (FORC) study on a Pt/Co/Fe/Ir magnetic stack that exhibited a magnetic phase transition from isolated skyrmions to skyrmion lattice with increasing temperature. Using in situ magneto-optical Kerr imaging, a generalized description of domain transformations associated with the FORC distribution peaks at both their reversal and sweeping field are derived to allow for direct analysis from the FORC diagram. The sweeping field of the peak, which is commonly ignored in analysis, is identified as the process of domain propagation or nucleation towards terminal domain separation. This process is found to be essential in inducing magnetization irreversibility to reveal domain transformations. In addition, a model characterized by the FORC distribution peaks was developed to describe the transition from the isolated skyrmion to skyrmion lattice phase as well as to identify important field ranges for the transformations. This study establishes an intuitive form of analysis for the otherwise abstract data of FORC distribution for the characterization of magnetic skyrmions in the active field of skyrmionics.